PENGARUH KEJUTAN SUHU TERHADAP MASA INKUBASI DAN DERAJAT PENETASAN TELUR ABALONE (Haliotis asinina) - Syafruddin Nasution; Rusdi Machrizal (Berkala Perikanan Terubuk, 2009)
The aims of this study were to understand the effect of thermal shock onthe incubation duration and hatching rate of abalone eggs. Experimental designemployed was the complete randomize design (CRD) with three treatment factorswith three replications. These treatment factors were the thermal shock of thedifferent temperatures namely 20o C, 26oC and 40oC. The result showed thatshock treatment have significant different among treatments on the incubationduration and hatching rate of abalone eggs. The shortest incubation duration foundon the treatment of 40oC (4,9 hours). While the longest incubation duration foundon the treatment of 20oC (6,67 hours). The highest hatching rate of eggs found onthe treatment of (26 oC (98 %), and the lowest hatching rate was on the treatmentof 20oC (87 %).